Analisis Kelayakan Usaha Percetakan: Studi Empiris Percetakan di Lingkungan Kampus Universitas Halu Oleo - Harjun Harjun; Rezki Amelia (Indo Publishing, 2026)
Photocopy and printing service businesses represent integral UMKM segment supporting academic activities of students in campus environment, yet face intensifying competition and shifting digital consumption landscape. This research analyzes feasibility of photocopy and printing businesses around Halu Oleo University through empirical approach integrating field observation, in-depth interviews, and structured questionnaires to consumers and business operators. Three photocopy businesses become investigation focus: Faris Jaya Foto Copy (revenue Rp20 million/month), FC Nusaibah Perdos UHO (unstable revenue), and Foto Copy Sarmin/Mangkerei (revenue Rp5-10 million/month), with fifteen consumer respondents. Mixed methods methodology combines operational observation, semi-structured interviews with owners for strategic exploration and challenges identification, and questionnaires with categorical rating scales to measure consumer satisfaction. Results demonstrate that photocopy businesses possess substantial feasibility with stable consumer demand (2-3 times/week), affordable expenditure (Rp5,000-Rp15,000/visit), and high satisfaction levels. Faris Jaya Foto Copy shows established position with stable revenue Rp20 million/month through competitive pricing and service consistency. FC Nusaibah Perdos UHO demonstrates aggressive market entry with diverse service offerings (photocopy, print, binding, laminating), despite experiencing revenue volatility. Foto Copy Sarmin/Mangkerei maintains viable operations with price-sensitive positioning. Dominant purchase decision factors include strategic location, service speed, print quality, and environmental cleanliness. Challenges include intense competition, equipment malfunction, raw material limitations, and infrastructure disruptions. Comprehensive recommendations include: robust infrastructure maintenance system implementation, systematic quality control adoption, digital marketing implementation for market reach expansion, and continuous service innovation for long-term sustainable competitive advantage.